Hidden Catholic collections (American Catholic Historical Society, 2002)
The ACHA’s Hidden Catholic Collections Project asked archivists and librarians to nominate collections in their holdings that they think have high historic value but might not receive as much scholarly attention as they should. By harnessing the power and reach of ACHA’s social media platforms and website, we have been shining the spotlight on a new collection each week this year. If you missed a week’s posting on Facebook, Twitter, or Instagram, this page will serve as an aggregator of that content. If you think a collection might be helpful to your research or you just see something you like, please reach out to the archivist or librarian to let them know!